Target similarity and gender difference: Effects of servant leadership on supervisory commitment and supervisory citizenship behavior - Phuoc Hong Nguyen; Long Thanh Nguyen; Linh Tran Cam Nguyen (IIM Ranchi Journal of Management Studies)
Purpose – This study applies the target similarity model to examine the effects of servant leadership on supervisor commitment and supervisor citizenship behavior. The mediating role of supervisory commitment is explored to determine the relationship between servant leadership and supervisor citizenship behavior. The difference in supervisor gender is examined in the linkage between servant leadership and supervisory commitment. Design/methodology/approach – The data were collected through a survey of 478 salespeople in the retail industry. Structural equation modeling (SEM) techniques were used to verify the hypotheses of this study. Findings – The findings showed significant support for the direct and indirect effects of servant leadership on supervisor commitment and supervisor citizenship behavior. Furthermore, the positive relationship between servant leadership and supervisory commitment was stronger among female supervisors than male supervisors. Originality/value – Due to the scarcity of studies conducted on the linkages of servant leadership, supervisory commitment and supervisory citizenship behavior, this study theoretically and empirically contributes to the leadership literature as it is the first study to investigate these direct and indirect relationships. Similarly, this study examined gender differences in servant leadership to fill the gap in the research field.